Hearsay Evidence and Reasons for its Inadmissibility in the Nigerian Adversarial Legal System - Olarinde, E. Smaranda; Idem, Udosen Jacob (ABUAD Law Journal, 2019)
At common law and in Nigeria, hearsay evidence arises where a witness in his own testimony makes a statement, oral or written made by another person who experienced, heard and saw an incident happen in order to establish the truth asserted. Such testimony is generally inadmissible because the informant who witnessed the event is not in court to prove the truth of his statement under oath. This paper examines what is hearsay evidence and further seeks to discuss exceptions to the rule and highlights reasons for its inadmissibility. The finding of this article is that hearsay evidence is weak and untrustworthy to be relied upon by the court, the same not being a testimony of a person who witnessed the event. The paper recommends that the Evidence Act be amended to provide for the range of offences that section 37 of Evidence Act can cover apart from exceptions mentioned in Sections 38-45.